The influence of pedagogical competence, lecturer communication style, and student involvement on student perceptions of lecturer teaching methods with learning motivation as a mediating variable (study on civil servants of UNJ East Jakarta Region) - Rusmia Butarbutar; A. Noesyirwan Moeis; Rahayu Endang Suryani; Farida Farida (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the role of learning motivation as a mediator variable in the influence of lecturers' pedagogical competence, lecturers' communication style, and student involvement on students' perceptions of lecturers' teaching methods for Civil Servant (PNS) students at Jakarta State University in East Jakarta. This study uses a quantitative approach with a survey method and explanatory research design. Data were collected through a Likert-based questionnaire distributed to 150 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). This study aims to analyze the role of learning motivation as a mediator variable in the influence of lecturers' pedagogical competence, lecturers' communication style, and student involvement on students' perceptions of lecturers' teaching methods for Civil Servant (PNS) students at Jakarta State University in East Jakarta. This study uses a quantitative approach with a survey method and explanatory research design. Data were collected through a Likert-based questionnaire distributed to 150 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS).